Stretchable and Soft Electroadhesion Using Liquid‐Metal Subsurface Microelectrodes. Issue 9 (25th June 2021) - Park, Sungjune; Shintake, Jun; Piskarev, Yegor; Wei, Yuwen; Joshipura, Ishan; Frey, Ethan; Neumann, Taylor; Floreano, Dario; Dickey, Michael D.
Abstract: Electroadhesion is an attractive mechanism to electrically modulate adhesion to surfaces. Electroadhesion arises from the interaction of electric fields with conductive or dielectric materials. Electroadhesion devices consist of in‐plane, interdigitated electrodes that generate out‐of‐plane electric fields, which increase adhesion with target surfaces. To date, these electrodes have predominantly been composed of carbonaceous materials. Here, liquid metal is utilized to create the electrodes in silicone substrates. Liquid metal can be patterned in a variety of unique ways, including microfluidic injection, spray deposition, or printing. These electrodes have nearly unlimited deformation in soft and stretchable substrates while maintaining metallic conductivity. The experimental results show that stretching improves electroadhesion performance due to the changes in geometry of the electrodes and insulation layer, whose behaviors are theoretically predictable. The use of liquid‐filled, sub‐surface microchannels can help to maintain contact between the elastomer and substrate during peeling due to the surface stresses caused by the capillary pressure. This approach to electroadhesion can be implemented in ultra‐stretchable and soft substrates, including those used in soft robotics, due to the inherently compliant and deformable electrical conductivity of the liquid metal electrodes. Abstract : Stretchable and soft electroadhesion is demonstrated by the use of liquid metal electrodes in elastomer. The devices increase electroadhesion force with strain due to favorable changes to the electrode geometry. The use of liquids also provides intrinsic enhancement by the surface stresses caused by the capillary pressure from the subsurface liquid metal.